(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article provides all the latest information about cardiovascular diseases. The article provides information on measures for the treatment of cardiovascular diseases and effective methods of prevention. Due to the fact that cardiovascular diseases are common among young people and elderly people, the statistics of this disease were also studied in the article.